Quantitative test method for sodium content in palladium-carbon catalyst

By mixing the palladium carbon catalyst sample with aqueous nitric acid solution and filtering it, combined with inductively coupled plasma emission spectroscopy, the problem of determining the sodium content in palladium carbon catalyst is solved, and a rapid and accurate quantitative test of sodium content is achieved.

CN119555452APending Publication Date: 2025-03-04SICHUAN XINDI PHARM CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411618214.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The prior art lacks relevant research methods for determining the sodium content in palladium carbon catalysts, resulting in the introduction of sodium ions into the product during hydrogenation reactions and other processes, making it difficult to completely remove the finished product, resulting in the product residue exceeding the standard.

Method used

The palladium carbon catalyst sample was mixed with 5-15% aqueous nitric acid solution, and then filtered after vigorous shaking, the filtrate was collected, and the sodium content in the filtrate was determined by inductively coupled plasma emission spectroscopy.

Benefits of technology

It realizes fast, simple, accurate and efficient quantitative testing of sodium content in palladium carbon catalyst, which is easy to operate, short processing time, good accuracy and repeatability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119555452A_ABST
    Figure CN119555452A_ABST
Patent Text Reader

Abstract

The invention is suitable for the technical field of metal analysis and detection, and provides a quantitative test method for the content of sodium in a palladium-carbon catalyst, and the quantitative test method for the content of sodium in the palladium-carbon catalyst comprises the following steps: mixing a palladium-carbon catalyst sample with a nitric acid aqueous solution to obtain a test solution; filtering the test solution, collecting filtrate, and measuring the content of sodium in the filtrate by using an inductively coupled plasma emission spectrum; wherein the concentration of the nitric acid aqueous solution is 5-15%. The sodium ions in the palladium-carbon catalyst sample are extracted by using the 5-15% nitric acid aqueous solution, and the sodium content in the filtrate is determined by combining the inductively coupled plasma emission spectrum, so that the operation is simple and rapid, the treatment time is short, and the accuracy and repeatability are good; the method is a pretreatment and quantitative analysis method for rapidly, efficiently and accurately measuring the sodium content in the palladium-carbon catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of metal analysis and detection, and in particular relates to a quantitative test method for the sodium content in a palladium-carbon catalyst. Background Art

[0002] There are few reports on the pretreatment and detection methods of sodium elements in palladium carbon catalysts in the prior art, and there are only relevant reports on the pretreatment and detection methods of palladium elements in palladium carbon. The pretreatment methods for palladium element detection in palladium carbon mainly include wet digestion method and dry ashing method-wet digestion method; among them, the wet digestion method is to use a large amount and multiple acids to digest the palladium carbon catalyst sample under high temperature and high pressure or normal pressure and high temperature conditions to achieve the release of palladium elements; the dry ashing method-wet digestion method first removes the activated carbon in the sample under high temperature conditions such as a temperature greater than 600°C, and then treats the ashing residue with acid to achieve complete digestion of the carbon element. However, both of the above methods are time-consuming and lengthy (more than 6 hours), and the operation is complicated, the reagent consumption is large, and the digestion solution needs to be diluted before the palladium element can be detected by inductively coupled plasma optical emission spectroscopy (ICP-OES).

[0003] Palladium-carbon catalysts are often used in various experimental reaction systems, such as hydrogenation reactions. During the reaction, sodium ions in the palladium-carbon catalyst will be introduced into the product, which is difficult to completely remove in post-treatment and finished products, resulting in excessive product residue. Therefore, when using palladium-carbon catalysts for related experiments, it is necessary to strictly control the sodium content in the palladium-carbon catalyst. However, the current existing technology lacks relevant research methods for determining the sodium content in palladium-carbon catalysts. Summary of the invention

[0004] The purpose of the embodiments of the present application is to provide a quantitative test method for the sodium content in a palladium-carbon catalyst, aiming to fill the research gap in the current prior art for determining the sodium content in a palladium-carbon catalyst.

[0005] The embodiment of the present application is implemented as follows: a quantitative test method for the sodium content in a palladium-carbon catalyst comprises:

[0006] The palladium carbon catalyst sample is mixed with an aqueous nitric acid solution to obtain a test solution.

[0007] Filtering the test solution, collecting the filtrate, and determining the sodium content in the filtrate by inductively coupled plasma emission spectroscopy;

[0008] Wherein, the concentration of the nitric acid aqueous solution is 5-15%.

[0009] Preferably, the step of mixing the palladium-carbon catalyst sample with an aqueous nitric acid solution to obtain a test solution comprises:

[0010] The palladium-carbon catalyst sample was mixed with the nitric acid aqueous solution and vigorously shaken for 0.5 min to obtain a test solution.

[0011] Preferably, the concentration of the test solution is 5 mg / mL.

[0012] Preferably, the concentration of the nitric acid aqueous solution is 5%.

[0013] The embodiment of the present application innovatively proposes a quantitative test method for the sodium content in a palladium-carbon catalyst. The sodium ions in the palladium-carbon catalyst sample are dissolved and extracted with a 5-15% nitric acid aqueous solution, and the sodium content in the filtrate is determined by combining inductively coupled plasma emission spectroscopy. The operation is simple and fast, the processing time is short, and the accuracy and repeatability are good. It is a pretreatment and quantitative analysis method for quickly, efficiently and accurately determining the sodium content in a palladium-carbon catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is a sodium concentration-intensity standard curve provided in the examples of the present application. DETAILED DESCRIPTION

[0015] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0016] The present application embodiment innovatively proposes a quantitative test method for the sodium content in a palladium-carbon catalyst, comprising:

[0017] The palladium-carbon catalyst sample is mixed with an aqueous nitric acid solution to obtain a test solution;

[0018] Filtering the test solution, collecting the filtrate, and determining the sodium content in the filtrate by inductively coupled plasma emission spectroscopy;

[0019] Wherein, the concentration of the nitric acid aqueous solution is 5-15%, preferably 5%.

[0020] Optionally, the step of mixing the palladium-carbon catalyst sample with an aqueous nitric acid solution to obtain a test solution comprises:

[0021] The palladium-carbon catalyst sample is mixed with the nitric acid aqueous solution and vigorously shaken for 0.5-15 minutes to obtain a test solution; preferably, the solution is vigorously shaken for 0.5 minutes.

[0022] Optionally, the concentration of the test solution is 5-20 mg / mL, preferably 5 mg / mL.

[0023] Optionally, the step of mixing the palladium-carbon catalyst sample with an aqueous nitric acid solution to obtain a test solution comprises:

[0024] Weigh 0.1 g of palladium-carbon catalyst sample and place it in a 10 mL container, dilute to volume with nitric acid aqueous solution, and shake vigorously for 0.5 min to obtain the test solution.

[0025] Optionally, filter the sample solution using a 0.2 μm PTFE or nylon needle filter.

[0026] The following specific examples are used to describe in detail the pretreatment and quantitative analysis method for determining the sodium content in the palladium-carbon catalyst, as shown below. The experimental methods used in the following examples are conventional methods unless otherwise specified; the materials, reagents, etc. used, unless otherwise specified, can all be obtained from commercial sources.

[0027] The test samples and impurity reference substances required for the verification of the following example methods are as follows:

[0028]

[0029] The chemical reagent information required for the verification of the following example methods is as follows:

[0030]

[0031] The instrument information required for the following example method is as follows:

[0032]

[0033] The spectral conditions of the inductively coupled plasma emission spectrometer used in the following example methods are as follows:

[0034]

[0035]

[0036] Example 1: Investigating the effect of different shaking extraction times on the detection results of sodium content in palladium-carbon catalyst

[0037] Prepare a series of sodium standard curve solutions, test the sodium concentration and intensity by 1CP-OES, and draw a sodium concentration-intensity standard curve. Weigh about 0.1g of palladium carbon catalyst sample, weigh 7 portions in parallel, place them in 7 10mL plastic volumetric bottles, dilute to scale with 10% nitric acid aqueous solution, and shake vigorously for 30s, 3min, 5min, 10min and 15min respectively. Investigate the situation of free sodium ions in the palladium carbon catalyst being dissolved and released in 10% nitric acid aqueous solution at different shaking times, filter immediately with 0.2um PTFE (or nylon) needle filter, collect the filtrate, and determine the sodium concentration in the filtrate by ICP-OES. The sodium content in the test sample is calculated by the standard curve method, and the test results are shown in Table 1.

[0038] Table 1 Sodium content test results at different shaking times

[0039]

[0040] As can be seen from Table 1, the shaking extraction time is 0.5min to 15min, and the sodium content results in the test samples differ by less than 10%, which can be considered to have no significant difference.

[0041] Example 2: Investigating the effect of different nitric acid concentrations on the sodium content detection results in palladium carbon catalyst

[0042] Prepare a series of sodium standard curve solutions, test the sodium concentration and intensity by ICP-OES, and draw a sodium concentration and intensity standard curve. Weigh about 0.1g of palladium carbon catalyst sample, weigh 8 portions in parallel, place them in 8 10mL plastic volumetric bottles, dilute to scale with 2%, 5%, 10%, and 15% nitric acid aqueous solutions, shake vigorously for 30s, and investigate the dissolution and release of free sodium ions in the palladium carbon catalyst in the nitric acid aqueous solution at different nitric acid concentrations. Immediately filter with a 0.2μm PTFE (or nylon) needle filter, collect the filtrate, and determine the sodium concentration in the filtrate by ICP-OES. Use the standard curve method to calculate the sodium content in the test sample.

[0043] Table 2 Detection results of sodium content at different nitrate concentrations

[0044]

[0045] As can be seen from Table 2, when the nitric acid concentration is 5% to 15%, the sodium content results in the test samples differ by less than 10%, and it can be considered that there is no significant difference.

[0046] Example 3: Investigating the influence of different palladium-carbon catalyst test sample concentrations on the sodium content test results

[0047] Prepare a series of sodium standard curve solutions, test the sodium concentration and intensity by ICP-OES, and draw a sodium concentration-intensity standard curve. Weigh about 0.05g, 0.1g, 0.15g, and 0.2g of palladium carbon catalyst samples, weigh 2 portions in parallel, and place them in 8 10mL plastic volumetric bottles, dilute to the scale with 10% nitric acid aqueous solution, and shake vigorously for 30s. Investigate the dissolution and release of free sodium ions in the palladium carbon catalyst in the nitric acid aqueous solution at different test sample concentrations, and immediately filter with a 0.2μm PTFE (or nylon) needle filter, collect the filtrate, and determine the sodium concentration in the filtrate by ICP-OES. The sodium content in the test sample was calculated using the standard curve method. The test results are shown in Table 3.

[0048] Table 3 Sodium content test results of different test sample concentrations

[0049]

[0050] As can be seen from Table 3, the concentration of the test sample is 5 mg / mL to 20 mg / mL, the concentration of sodium in the test sample solution is linear, and the sodium content results in the test samples differ within 10%, which can be considered to have no significant difference.

[0051] Example 4: Accuracy experiment of spike recovery: weigh about 0.1g palladium carbon catalyst sample in a 10mL plastic volumetric flask, weigh 9 portions in parallel, add a certain volume of 100μg / mL sodium element stock solution (preparation process as shown in Table 4) to the volumetric flask respectively, dilute to scale with 10% nitric acid aqueous solution, shake vigorously for 30s, so that free sodium ions in the palladium carbon catalyst are dissolved and released in 10% nitric acid aqueous solution, filter immediately with 0.2μmPTFE (or nylon) needle filter, collect filtrate, and measure the sodium element concentration in the filtrate by ICP-OES. According to the sodium content in the test sample and the addition amount of standard sodium element, calculate the spike recovery, and the results are shown in Table 5.

[0052] Table 4 Accuracy solution preparation schedule

[0053]

[0054] Table 5 Accuracy (spike recovery) experimental results

[0055]

[0056]

[0057] As can be seen from Table 5, the spiked recoveries were all between 70% and 130%, the results were accurate and reliable, and the RSDs were all less than 10%, indicating that the detection method of the present application had good accuracy.

[0058] Example 5: Repeatability and intermediate precision experiments

[0059] Prepare a series of sodium standard curve solutions, test the sodium concentration and intensity by ICP-OES, and draw a sodium concentration and intensity standard curve. Weigh about 0.1g of palladium carbon catalyst sample into a 10ml plastic volumetric flask, dilute to the scale with 10% nitric acid aqueous solution, shake vigorously for 30s to facilitate the dissolution of free sodium ions in the palladium carbon catalyst and release them in the 10% nitric acid aqueous solution, immediately filter with a 0.2μm PTFE (or nylon) needle filter, collect the filtrate, and determine the sodium concentration in the filtrate by ICP-OES. Two people each prepare 6 copies in parallel. Use the standard curve method to calculate the sodium content in the test sample and calculate the RSD. The results are shown in Table 6.

[0060] Table 6 Repeatability and intermediate precision experimental results

[0061]

[0062] As can be seen from Table 6, the RSD of the 6 parallel test results by a single person did not exceed 5%, and the RSD of the 12 parallel test results by two people did not exceed 10%, indicating that the repeatability and intermediate precision of the detection method of the present application are good.

[0063] Example 6: Durability Test

[0064] (1) Prepare a series of sodium standard curve solutions, test the sodium concentration and intensity by ICP-OES, and draw a sodium concentration-intensity standard curve. Weigh about 0.5g of palladium carbon catalyst sample into a 50mL plastic volumetric flask, dilute to the scale with 10% nitric acid aqueous solution, shake vigorously for 30s to facilitate the dissolution of free sodium ions in the palladium carbon catalyst and release them in the 10% nitric acid aqueous solution, immediately filter with a 0.2μm PTFE (or nylon) needle filter, collect the filtrate, and use ICP-OES to determine the sodium concentration in the filtrate. The standard curve method is used to calculate the sodium content in the test sample. Investigate the ICP-OES instrument parameters: when the nebulizer gas flow rate is 0.50L / min and the RF power is 1150w±50w, the sodium content in the palladium carbon catalyst. The test results are shown in Table 7.

[0065] (2) Prepare a series of sodium standard curve solutions, test the sodium concentration and intensity by ICP-OES, and draw a sodium concentration-intensity standard curve. Weigh about 0.5g of palladium carbon catalyst sample into a 50mL plastic volumetric flask, dilute to the scale with 10% nitric acid aqueous solution, shake vigorously for 30s to facilitate the dissolution of free sodium ions in the palladium carbon catalyst and release them in the 10% nitric acid aqueous solution, immediately filter with a 0.2μm PTFE (or nylon) needle filter, collect the filtrate, and use ICP-OES to determine the sodium concentration in the filtrate. The standard curve method is used to calculate the sodium content in the test sample. Investigate the ICP-OES instrument parameters: when the RF power is 1150w, the nebulizer gas flow rate is 0.50L / min±0.1L / min, and the sodium content in the palladium carbon catalyst. The test results are shown in Table 7.

[0066] Table 7 Durability test results

[0067]

[0068]

[0069] The configurations of the reference solution and the standard curve solution involved in the above embodiments of the present application are as follows:

[0070] Reference solution: Accurately measure 1.0 mL of sodium single element standard solution (1000 μg / mL), place in a 10 mL volumetric flask, dilute to scale with 10% nitric acid solution, and shake well. (Concentration is 100 μg / mL)

[0071] Standard curve solution: Accurately pipette a certain volume of sodium element stock solution and place it in a certain volume volumetric flask. Dilute it to the scale with diluent according to Table 8 below, shake well, and the solution is ready.

[0072] Table 8 Sodium standard linearity test solution preparation schedule

[0073]

[0074] Determination: The prepared series of sodium standard curve solutions are tested for sodium concentration and intensity by ICP-OES, and a sodium concentration-intensity standard curve is drawn, such as Figure 1 As shown, the equation is f(x)=292526.5652*x+11443.4462, R 2 =0.9996.

[0075] Example 7: Comparison of pre-treatment methods for detecting sodium content in different palladium-carbon catalysts

[0076] Method 1: Ashing, formic acid, and aqueous regia solution pretreatment

[0077] Take 0.1g palladium carbon (wet basis) in a porcelain crucible, place it in a muffle furnace at 850℃ and completely ash it (about 6h), add 5mL formic acid to the completely ashed palladium carbon catalyst, cover it with a watch glass, heat it at 60℃ in a water bath until it is wet salt, then add 10mL aqua regia (volume ratio of hydrochloric acid to nitric acid is 3:1), heat it at low temperature to dissolve and drive away the excess acid, remove it and cool it, rinse the watch glass and crucible with purified water, transfer the solution to a 10mL volumetric flask, make up to volume with purified water, shake it well, and detect the sodium content by ICP-OES. The test results are shown in Table 9.

[0078] Method 2: Pre-treatment before electric furnace burning

[0079] Weigh 0.1g of palladium carbon catalyst into a porcelain crucible, and weigh 9 portions in parallel. Add 0.125mL 100μg / mL sodium standard solution to 3 portions, add 0.25mL 100μg / mL sodium standard solution to 3 portions, and add 0.375mL 100μg / mL sodium standard solution to the other 3 portions. Place them on an electric furnace and burn for about 1h. After cooling, dissolve and extract sodium ions with nitric acid aqueous solution, and detect the sodium content by ICP-OES. In addition, 3 crucibles were not added with palladium carbon catalyst test samples. 0.125mL 100μg / mL sodium standard solution, 0.25mL 100μg / mL sodium standard solution, and 0.375mL 100μg / mL sodium standard solution were added thereto respectively. Burn on an electric furnace for about 1h. After cooling, dilute with nitric acid aqueous solution and transfer to 10mL. Detect the sodium content by ICP-OES. The test results are shown in Table 10.

[0080] Method 3: Pre-treatment method of the above embodiment of the present application

[0081] Weigh 0.1g of palladium carbon catalyst in a 10mL volumetric flask, weigh 11 portions in parallel, 2 portions without sodium standard solution, 3 portions with 0.125mL 100μg / mL sodium standard solution, 3 portions with 0.25mL 100μg / mL sodium standard solution, and 3 portions with 0.375mL 100μg / mL sodium standard solution, mix with 10% nitric acid aqueous solution, extract sodium ions in the palladium carbon catalyst, collect the filtrate after filtering, and use ICP-OES to determine the sodium content in the filtrate. The test results are shown in Table 9.

[0082] Table 9 Test results of method 1 and method 3

[0083]

[0084]

[0085] Table 10 Test results of method 2

[0086]

[0087]

[0088] As can be seen from Tables 9-10, there is a loss of sodium in the sample pre-treated by Method 1, and the tested content is only half of the sodium content in the sample treated by the wet method. In the palladium carbon catalyst test sample filtrate with a spiked amount of 25μg and 37.5μg of sodium standard solution in Method 2, the actual total amount of sodium tested is lower than the theoretical amount of sodium added, and the recovery rate of the sodium standard solution is less than 30%, indicating that the accuracy of the pre-incineration treatment method is not high. The experimental results of the spiked recovery rate of Method 3, i.e. the method of this application, can reach 70%-130%, which takes less time and has more accurate results.

[0089] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.

[0090] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A quantitative test method for sodium content in a palladium-carbon catalyst, characterized in that: include: The palladium carbon catalyst sample is mixed with an aqueous nitric acid solution to obtain a test solution. Filtering the test solution, collecting the filtrate, and determining the sodium content in the filtrate by inductively coupled plasma emission spectroscopy; Wherein, the concentration of the nitric acid aqueous solution is 5-15%.

2. The quantitative test method for sodium content in the palladium-carbon catalyst according to claim 1, characterized in that, The step of mixing the palladium-carbon catalyst sample with an aqueous nitric acid solution to obtain a test solution comprises: The palladium-carbon catalyst sample was mixed with the nitric acid aqueous solution and vigorously shaken for 0.5-15 min to obtain a test solution.

3. The quantitative test method of sodium content in the palladium-carbon catalyst according to claim 2, characterized in that, Shake vigorously for 0.5 min.

4. The quantitative test method for sodium content in the palladium-carbon catalyst according to claim 1, characterized in that, The concentration of the test solution is 5-20 mg / mL.

5. The quantitative test method for sodium content in the palladium-carbon catalyst according to claim 4, characterized in that, The concentration of the test solution is 5 mg / mL.

6. The quantitative test method for sodium content in the palladium-carbon catalyst according to claim 1, characterized in that, The concentration of the nitric acid aqueous solution is 5%.

7. The quantitative test method for sodium content in the palladium-carbon catalyst according to claim 1, characterized in that, The step of mixing the palladium-carbon catalyst sample with an aqueous nitric acid solution to obtain a test solution comprises: Weigh 0.1 g of palladium-carbon catalyst sample and place it in a 10 mL container, dilute to volume with nitric acid aqueous solution, and shake vigorously for 0.5 min to obtain the test solution.

8. The quantitative test method for sodium content in the palladium-carbon catalyst according to claim 1, characterized in that, Filter the sample solution with a 0.2 μm PTFE or nylon needle filter.